Prospects and Techniques of Regenerative Current Breaking in DC Circuit Breaker Topology - Sanzad Lumen, S.M. (Institute of Electrical and Electronics Engineers Inc., 2021)
DC power system has gained vast popularity thanks to the enormous development of power electronics. DC converters, appliances, equipment etc. are also getting immense attention in the research arena. Protecting a DC power system from fault is an emerging area that needs to be explored and developed further. DC Circuit Breaker (DCCB) is one such sophisticated technology that plays a very important role in circuit protection as well as in normal load switching. But its quite challenging to design a dc circuit breaker. First of all, unlike AC current, DC current does not have any natural zero crossing point hence, this current can not be broken safely by conventional AC circuit breaker. Furthermore, DC network possesses a significant amount of network inductances which stores energy in terms of current. Sudden current breaking during DCCB tripping is opposed by this stored energy. Hence, this energy needs to be removed from the network and literature review shows that all the conventional topologies dissipate this stored energy as heat by using either snubber network or nonlinear resistor. However, this energy can be stored and reused later by using reactive element instead of resistive element. The prospects and technique of energy recovery and reuse in a DCCB is studied in this paper and accordingly a new DCCB topology with energy regeneration capability is proposed. The proposed topology is capable of feeding the stored energy of the network back into the same network during every current breaking operation. Â© 2021 IEEE.